The chronological development of the theory of the firm, theory of entrepreneurship and theory of social entrepreneurship - Azan, Zaliza; Mhd. Sarif, Suhaimi (Human Research Management, Academic Research Society (HRMAR), 2017)
The paper explores conceptually the chronological development of the theory of the firm, the theory of entrepreneurship and theory of social entrepreneurship. This theories constructs were explained to provide the important part of the development based on economic circumstances. This paper allows researchers to get the main ideas from the pioneer stage until current enlargement under the theory of the firm, the theory of entrepreneurship and theory of social entrepreneurship with the moderate information. Theoretically, learning the early stages of these theories allows flexible and focused for all enterprises to perform better. Social entrepreneurship with the hybrid corporate objectives requires more understanding towards this theory for sustainability and increase competitive advantage.